2018
DOI: 10.1016/j.ejmp.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A constrained linear regression optimization algorithm for diaphragm motion tracking with cone beam CT projections

Abstract: The new algorithm will provide a potential solution to rendering diaphragm motion and possibly aiding the tumor target tracking in radiation therapy of thoracic/abdominal cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Similarly, tumor localization errors ranging over 0.6-4.3 mm were observed in Ref. 20 for fiducial markers. However, 3D motion models were built only to demonstrate the feasibility of real-time tracking for targets influenced by respiratory motion and their precision should be read within this context.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Similarly, tumor localization errors ranging over 0.6-4.3 mm were observed in Ref. 20 for fiducial markers. However, 3D motion models were built only to demonstrate the feasibility of real-time tracking for targets influenced by respiratory motion and their precision should be read within this context.…”
Section: Discussionsupporting
confidence: 58%
“…Previously reported tracking algorithms typically rely on a thresholding technique or impose various optimization constraints during imaging. For instance, in a recent paper, diaphragm identification was considered as a constrained linear regression optimization problem . Under this approach, thresholding was achieved using Otsu's method, the geometry was approximated by parabolas and the temporal redundancy of diaphragmatic motion was modelled by applying both band and algebraic constraints.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the problem with tracking tumor motion in fluoroscopic images is that it is difficult to identify tumor targets because of the poor image contrast. The upper edge of the diaphragm is sharp in contrast to the neighboring tissue and, therefore, can be more reliably identified than the tumor in the abdominal region (11). Studies have reported that tumor motion near the diaphragm has a high correlation with diaphragm motion, suggesting that the diaphragm could be used as an internal surrogate for predicting tumor motion without the need for fiducial implants (12,13).…”
Section: Introductionmentioning
confidence: 99%